Granulomatous Mediastinal Lymphadenitis Due to *M. avium* Infection with Progression to Systemic NTM Disease: A Case Report - Claudia Weber; Rosamaria Fulchini; Cyrill Rütsche; Martin Stöckli (healthbook TIMES Das Schweizer Ärztejournal Journal Des Médecins Suisses)
Nontuberculous mycobacteria (NTM) can cause pulmonary disease or lymphadenitis, the latter being more common in pediatric patients, among other sites of infection. The detection of nontuberculous mycobacteria does not necessarily indicate a clinically relevant infection requiring treatment, as NTM may be contaminants (e.g., from water sources) or cause asymptomatic infections. We describe the case of a 58-year-old male patient with granulomatous mediastinal and hilar lymphadenopathy, who had repeated detection of *Mycobacterium avium (M. avium)* without clear indications for NTM lung disease. Initial antibiotic treatment had to be discontinued due to severe adverse effects. Clinically and radiologically, there was no sign of disease progression over a short monitoring period. However, one year later, after the diagnosis of hairy cell leukemia, the disease progressed to disseminated NTM infection. Mediastinal tuberculous lymphadenitis is common and can be diagnosed using EBUS-TBNA samples. Isolated NTM mediastinal lymphadenitis is rarely described in the literature, and no recommendations exist regarding potential management for immunocompetent or immunocompromised patients. This case illustrates the diagnostic and therapeutic challenges of isolated NTM lymphadenitis in adults and highlights the importance of evaluating for underlying immunodeficiency.